The influence of age categories on performance parameters during on-court testing in wheelchair basketball players - Honnorat, L.; Weissland, T.; Pradon, D.; Alberca, I. A.; Rivière, J. R.; Brassart, F.; Vigié, O.; Faupin, A. (Frontiers in Sports and Active Living, 2025)
Introduction: Wheelchair basketball is a highly dynamic sport that requires optimized propulsion techniques, sprint performance, and fatigue resistance. Understanding the biomechanical differences between age groups is crucial for potential estimation and training optimization. This study aimed to analyze the impact of age on sprint performances by comparing junior and senior wheelchair basketball players, while also identifying factors influencing sprint performances beyond age, such as experience, wheelchair characteristics, and classification.